Understanding the context for agriculture for nutrition research: Identifying country typologies of child-stunting determinants - Maruyama, Eduardo; Unnevehr, Laurian J.; Wang, Jiarui (International Food Policy Research Institute, 2014)
We use data from 52 countries on child stunting, poverty, determinants of food security, environmental health, and quality of maternal and child care to carry out a cluster analysis of country typologies. The purpose is to identify where agriculture-led interventions might address binding constraints to progress in improving nutrition outcomes and to identify how existing research on the links between agriculture and nutrition in particular country contexts may or may not be representative.